2022
DOI: 10.1002/anbr.202100140
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Graphene Sensor Platform for the Detection of Viral Proteins in Low Volume Samples

Abstract: Infectious disease outbreaks remain an ever-prevalent global issue, with increasing global travel and trade increasing the risk of rapid disease spread to pandemic levels. [1] This is exemplified by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic from 2019. One specific issue that has been highlighted by the pandemic is the need for methods to achieve rapid, accurate diagnostics for infectious diseases, not just for coronaviruses, but for other major diseases as well. Rapid diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…224 Walters et al reported an Au Please do not adjust margins Please do not adjust margins nanoparticle functionalized graphene resistor sensor to detect the Hepatitis C virus core antigen (HCVcAg) in real-time. 225 The sensor demonstrates good sensitivity to the HCVcAg higher than 100 pg mL -1 . In another work, LIG was functionalized with pyrenebutyric acid (PBA) as a linker to immobilization of the antibodies to specifically detect biomarkers including SARS-CoV-2 nucleocapsid protein (NP), immunoglobulins (Igs) against SARS-CoV-2 spike protein and C-reactive protein.…”
Section: Applicationsmentioning
confidence: 94%
“…224 Walters et al reported an Au Please do not adjust margins Please do not adjust margins nanoparticle functionalized graphene resistor sensor to detect the Hepatitis C virus core antigen (HCVcAg) in real-time. 225 The sensor demonstrates good sensitivity to the HCVcAg higher than 100 pg mL -1 . In another work, LIG was functionalized with pyrenebutyric acid (PBA) as a linker to immobilization of the antibodies to specifically detect biomarkers including SARS-CoV-2 nucleocapsid protein (NP), immunoglobulins (Igs) against SARS-CoV-2 spike protein and C-reactive protein.…”
Section: Applicationsmentioning
confidence: 94%
“… 157 In this study, an rGO-based field-effect transistor (2DBioFET) was biofunctionalized with molecules that selectively bind to a malaria biomarker, i.e., Plasmodium falciparum lactate dehydrogenase (PfLDH), with a detection limit down to 0.11 pg/mL. Similarly, Walters et al developed a graphene sensor platform for rapidly diagnosing the hepatitis virus, 158 and reported a detection limit down to 100 pg/mL in less than 4 min, even with smaller volume samples, i.e., 5 μL. The sensor is easily adaptable to other infectious disease markers, such as hepatitis B virus, SARS-CoV-2, HIV, and many others.…”
Section: Applications Of Graphenementioning
confidence: 99%